Understanding employee creativity from the perspectives of grit, work engagement, person organization fit, and feedback - Gonlepa, Miapeh Kous; Dilawar, Sana; Amosun, Tunde Simeon (Frontiers in Psychology, 2023)
Purpose Drawing on the growing emphasis in the literature on the importance of creativity in the workplace, the present study examines the effect of personal and organizational level factors that influences employee creativity. Precisely, we examine how grit, work engagement, person-organization fit, and feedback influence creativity in the workplace. Design/methodology/approach We sampled data from 422 research assistants who are professional workers at top-notch Universities in China. They were recruited to participate in the survey through an online medium known as WeChat. We empirically tested the effect of grit, work engagement, person-organization fit, and feedback on employee creativity. These hypotheses were supported by confirmatory and exploratory factor analysis, and path analysis. Findings The results show that work engagement strengthens the relationship between grit and creativity. In addition, the results proved that person-organization fit positively moderates the link between grit and work engagement. Feedback also had a positive mediating effect on the link between work engagement and creativity. Practical implications Based on the appropriateness of an individual work environment, a gritty person will likely become engaged and creative with task execution. Consequently, a person’s organizational fit will strongly interact with grit, work engagement, and creativity. Originality/value We shed light on the blended value of personal and organizational-level factors that positively affect creativity in the workplace. Specifically, grit being both a personal and organizational factor influences employee creativity via work engagement. This research explored the effect of work engagement as a mechanism that serves as a motivational feature enhancing creativity. We also simultaneously identify the moderation conditions of person-organization fit and feedback. The theoretical and practical implications of the findings are discussed in detail. The study makes a theoretical contribution through its assessment of the impact of grit on employee creativity. The trait activation theory portrays how grit can be expressed through feedback and person-organization fit. In terms of practice, grit can be an important consideration in hiring decisions, and feedback should be given to make the workplace more creative.